Pengaruh Total Arus Kas Dan Pertumbuhan Penjualan Terhadap Harga Saham Pada Perusahaan Sub Sektor Makanan Dan Minuman Yang Terdaftar Di Bei Periode 2016-2020 - Sulastri, Sulastri (CV. ITTC INDONESIA, 2022)
The purpose of this study was to test and determine the effect of total cash flow and sales growth on stock prices. The object of this research is the food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the 2016-2020 period. This type of research is quantitative, namely research that emphasizes theory testing through measuring research variables with numbers and analyzing data using statistical procedures. In this study, sampling using purposive sampling based on predetermined characteristics of 13 companies. The type of data used is secondary data obtained from the financial statements of each company with a total of 65 data observations. Data analysis using SPSS version 25 program. The results based on the results of hypothesis testing indicate that the total cash flow variable partially has a significant effect on stock prices which has a t value of 2.862 and a significant value of 0.006 < 0.05. Sales growth partially has no significant effect. to the stock price which has a t value of 0.328 and a significant value of 0.744> 0.05. For simultaneous testing, the result is that total cash flow and sales growth have a significant effect on stock prices which have a significant value of 0.020 <0.05. From the discussion, it can be concluded that as the amount of cash flow increases, the price also causes an increase. This proves that the explanation of cash flow information can actually generate added value for users of financial statement information.